Kingdom of Eswatini : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Kingdom of Eswatini. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
The COVID-19 pandemic is having a severe impact on Eswatini's economy at a time when the country is already facing deep economic challenges, and the government has begun fiscal consolidation efforts. A national lockdown to contain the spread of the virus, disruptions in supply chains, and lower external demand for key exports are curtailing economic activity. While the authorities' policy response has been timely and proactive, the economic shock and containment policies are triggering a severe recession with significant social costs, and have created urgent balance of payments needs. The pandemic is unfolding in a context of high prevalence of HIV/AIDS and a stretched health care system, which increase Eswatini's vulnerability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet